nurhidayah THE CORELATION OF CONFORMITY WITH CONSUMPTIVE BEHAVIOR IN YOUNG WOMEN OF XI CLASS SENIOR HIGH SCHOOL 2 TRENGGALEK: THE CORELATION OF CONFORMITY WITH CONSUMPTIVE BEHAVIOR IN YOUNG WOMEN OF XI CLASS SENIOR HIGH SCHOOL 2 TRENGGALEK - nurhidayah, nurhidayah (Universitas Nusantara PGRI Kediri, 2017)
Teenager is a dynamic development phase in the life of the individual. This period is a transition period of the children into maturity which characterized by the mental acceleration, emotional and social. The objective of this research is to know the relationship of conformity with consumptive behavior in young women of XI Class Senior High School 2 Trenggalek. This research use analytic corelation design with cross sectional approach. The population in this study are young women student of XI Class Senior High School 2 Trenggalekby using Purposive Sampling technique. The independent variable is aconformityand the dependent variableis a consumptive behavior. Data capture the dependent variables and independent variables using a questionnaire and analyzed with the test Spearmen's Rho Correlation with the level of significance of a≤ 0.10. The results showed that nearly half of young young women student of XI Class Senior High School 2 Trenggalek had high conformity i.e. 55 (44.7%) of the respondents, and nearly half of young women student of XI Class Senior High School 2 Trenggalek consumptive behavior has being namely 54 (36.7%) respondents. The results of statistical tests Spearman's Rho obtained sig (p) = 0000 <a= 0.896 correlation value 0.05. This means that H0 is rejected and the H1 is accepted. The conclusions of this research are no relationship with consumptive behavior conformity in young women of XI Class Senior High School 2 Trenggalek. To keep control of the personality of young women so as not to get stuck with conformity and consumptive behavior, then the expected health officers work closely with the school to conduct educator against students on a regular basis.